The impact of digitization on the formation of new forms of work - Samoraj-Charitonow, Beata (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
Digital transformation is radically changing the contemporary labor market, introducing dynamic employment models based on information technologies. The COVID-19 pandemic accelerated these changes, forcing the adaptation to digital communication and management tools. As a result, the number of people working remotely has increased, and new forms of work, such as platform work (gig economy) or cloud working, are redefining the traditional concept of employment. Automation and digitization generate both concerns about job losses and new professional opportunities, especially for individuals who previously faced difficulties entering or remaining in the labor market, including people with disabilities. New professions are emerging, such as cybersecurity specialists or digital marketing experts, which requires adjustments in labor laws and educational policies to meet the demands of the 4.0 economy. At the same time, digitization brings new challenges, such as task fragmentation, threats to employee autonomy, digital surveillance, and inequalities in access to technology. The introduction of new regulations, such as the EU platform work directive or the right to disconnect, aims to protect workers from the negative effects of digitization, such as burnout or the erosion of work-life balance. Promoting lifelong learning models and adapting legal regulations to the dynamically changing digital reality are crucial to ensuring a fair and efficient labor market in the digital age.